Humate-Coated Urea as a Tool to Decrease Nitrogen Losses in Soil - Konstantin Korsakov; Alexey Stepanov; Lev Pozdnyakov; Olga Yakimenko (Agronomy, 2023)
Processes of N transformation in soil as affected by application of the three kinds of urea fertilizers, conventional urea (U), humate-coated urea (U_HA), and urea treated with the urease inhibitor NBPT (U_UI), are examined in a model laboratory experiment. Effects of urea fertilizers on soil chemical (content of water-extractable N-NH4 and N-NO3), and microbiological properties (rate of actual and potential N2O emission, basal and substrate-induced respiration, microbial biomass C, emission of ethylene) are focused to answer the following questions: (i) whether humate-coated urea has the ability to decrease N losses in soil; and (ii) how it affects soil biological activity comparable to synthetic urease inhibitor. The results showed that U_HA demonstrated advantages comparable to U in its ability to decrease N losses in soil: it increased N-NH4 content by 35%, reduced nitrate content by 9%, and decreased N2O emissions by 50%. U_HA promoted basal soil respiration by 10% and the specific activity of the soil microbial community by 7%, providing the highest metabolic quotient qCO2. Comparably to NBPT-treated U, U_HA mainly shows intermediate results between U-UI and conventional U. Considering the low cost of raw humates, U-HA can be regarded as a promising tool to decrease N losses in soils.